Routledge Handbook of Asian Migrations
1 online resource
Keywords: "Housing more than half of the global population, Asia is a region characterised by increasingly diverse forms of migration and mobility. Offering a wide-ranging overview of the field of Asian migrations, this new handbook therefore seeks to examine and evaluate the flows of movement within Asia, as well as into and out of the continent. Through in-depth analysis of both empirical and theoretical developments in the field, it includes key examples and trends such as British colonialism, Chinese diaspora, labour migration, the movement of women, and recent student migration. Organised into thematic parts, the topics cover:The historical context to migration in AsiaModern Asian migration pathways and characteristicsThe reconceptualising of migration through Asian experiencesContemporary challenges and controversies in Asian migration practice and policyContributing to the retheorising of the subject area of international migration from non-western experience, the Routledge Handbook of Asian Migrations will be useful to students and scholars of migration, Asian development and Asian Studies in general."--Provided by publisher.